2012
DOI: 10.1002/pssb.201248387
|View full text |Cite
|
Sign up to set email alerts
|

Strain profiles and radii of semiconductor rolled‐up tubes made by a single material

Abstract: Single‐material rolled‐up microtubes provide an opportunity to study the processes of strain relaxation and defect formation near the interface of strained‐layer semiconductor heterostructures. We study theoretically tubes formed by a single strained Si layer grown beyond the critical thickness on a Ge substrate. The residual strain accumulated in the Si layer causes the layer to roll after it is released from the substrate by etching. Computer simulations are carried out using Keating's valence force field me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This corresponds to the other experiment results. One study reported that the residual strain varied between 4.2% and zero, and maximum strain happened at the silicongermanium interface [12]. Another study demonstrated that the growth eigenstrain of LPCVD (low-pressure chemical vapor deposition) polysilicon film at 615 °C was not uniform through the thickness, but decreased from 9 × 10 -4 to about zero as the deposited film thickness increased [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to the other experiment results. One study reported that the residual strain varied between 4.2% and zero, and maximum strain happened at the silicongermanium interface [12]. Another study demonstrated that the growth eigenstrain of LPCVD (low-pressure chemical vapor deposition) polysilicon film at 615 °C was not uniform through the thickness, but decreased from 9 × 10 -4 to about zero as the deposited film thickness increased [15].…”
Section: Resultsmentioning
confidence: 99%
“…A concept to make self-positioned micromachined structures by using the strain in a pair of lattice-mismatched epitaxial layers has been introduced [9]. Curvature estimation for the hinged multilayer structure with lattice mismatch strain has been investigated and the strain profile throughout the layered thickness has been demonstrated [10][11][12]. However, only the cases with initial strain due to the lattice mismatch or thermal loading were accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that the mismatch strain of LPCVD polysilicon film at 615 °C was not uniform through the thickness and decreased 9 × 10 -4 to about zero when the deposited film thickness increased [35]. Another study reported that the residual strain varied between 4.2% and zero, and maximum strain occurred at the Si/Ge interface [36]. One of the possible sources for mismatch strain is the lattice misfit, defined as = − f a a a ( )/ , s f s where a s (5.430 Å) and a f (3.520 Å) are the lattice constant of the silicon and film, respectively.…”
Section: Resultsmentioning
confidence: 99%